Corporate social responsibility, reputation and performance in the mining sector in Zimbabwe - Zuva, Joseph (Vaal University of Technology, 2022)
The world over the concept of corporate social responsibility (CSR) has gradually evolved from a theoretical concept to a managerial tool used to shape organisational competitiveness. Thus, this study sought to establish the influence of CSR on reputation and performance in the mining sector in Zimbabwe, given the limited evidence of such studies in the body of knowledge. The framework for data collection, presentation, analysis and interpretation was guided by the positivist paradigm, quantitative approach, and descriptive survey design. With the questionnaire being utilised to collect data from 330 respondents who were purposively and conveniently sampled from the targeted mines. The Cronbach Alpha coefficient was employed to test for the validity and reliability of the designed instrument. In addition, the Pearson’s correlation was used to determine relationships between constructs, while regression analysis was used to predict the reputation value based on causality. In addition, Exploratory Factor Analysis (EFA) was performed to determine the factor structure of the data collected based on the relationship of constructs and items. The analysed data revealed that most respondents, through descriptive statistics, agreed with the construct items except political corporate social responsibility (PCSR), which had the least mean score of (4.7311). This implied that the respondents somewhat agreed PCSR was being observed though at marginal levels. The other constructs stakeholder corporate social responsibility (SCSR), environment corporate social responsibility (ENCSR), ethical corporate social responsibility (ETCSR), and social corporate responsibility (SOCSR) had mean scores above 4, indicating that respondents agreed that CSR was being observed to retain a reputable image. Furthermore, regression analysis revealed that four of the stated hypotheses supported the assumption on SCSR, ETCSR, operational performance (OP), and social performance (SP). Furthermore, the results revealed that PCSR, ENCSR, SOCSR, and economic performance (EP) could not be used to support reputation. The results on the hypotheses statements confirmed the empirical literature assumptions. Thus, partnerships, trust, honesty, disclosure, competitive advantage, operational efficiency, values based on morality, and transparency were confirmed to be by-products of CSR practices. Based on this, it can be argued that mining firms in Zimbabwe could employ CSR as a strategic tool to handle stakeholders’ concerns. In this regard, a theoretical model was crafted for the mining sector in Zimbabwe, which reduced independent variables to two, namely the SCSR and ETCSR. Hence the results established a strong positive association between PSCR, SCSR, SOCSR, ENCSR, ETCSR, and corporate reputation (CR). In addition, corporate performance was seen to have a positive impact on OP and SP. Based on the above results, it is recommended that mining companies in Zimbabwe fully embrace CSR as a vehicle for engaging with stakeholders. More so, CSR programmes should be done in consultation with stakeholders, especially surrounding communities that host or provide an operating environment. Furthermore, mining companies should be wary of the cultural effects of their operations through the crafting and implementation of ethical policies. This can further be enhanced through CSR reporting on CSR initiatives and programmes.
Ph. D. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Corporate reputation; Corporate performance; Corporate social responsibility; Mining industry; Social exchange theory; Stakeholder theory; Dissertations, Academic -- South Africa.; Mineral industries -- Zimbabwe.; Social responsibility of business.